Dietary intake according to hydration status in 9-10 year-old soccer players - Lusmar Rodriguez (2016)
Introduction: Children have an increased risk of voluntary dehydration especially during physical activity which may increase the risk of non-compensating water losses. Objectives: The aim of this study was to assess the hydration status and its relation to food intake in a children group of soccer players. Method: A sample of 36 boys aged 9-10 years was included in this study; 30 completed a 24 h urine collection. Participants completed a 24 h urine collection; a 24 hours food recall corresponding to the day of urine collection was applied, weight and height were measured and parents/caregivers fi lled a lifestyle and socio-demographic questionnaire. The free water reserve (FWR [ml/24 h] =urine volume [ml/24 h] - obligatory urine volume [ml/24 h]) was used to assess the hydration status. Food and beverage groups were created and models of unconditional logistic regression were fi tted in order to estimate the magnitude of the association between the hydration status and diet. Results: Forty three per cent of participants were classifi ed as at risk of hypohydration. Children who reported a high fruit and vegetables intake (above the median) were at decreased risk of hypohydration (OR = 0.19, 95% CI 0.04-0.94, p = 0.041), compared to children who reported a low fruit and vegetables intake. Conclusions: Almost half of the children were at risk of hypohydration. Our results suggested that water food sources such as fruit and vegetables may contribute to euhydration.